Influence of remote ischemic conditioning and tramadol hydrochloride on oxidative stress in kidney ischemia/reperfusion injury in rats - Oliveira,Rita de Cássia Silva de (2017)
Abstract Purpose: To evaluate the effects of tramadol hydrochloride associated to remote ischemic perconditioning on oxidative stress. Methods: Twenty five male rats (Wistar) underwent right nephrectomy and were distributed into five groups: Sham group (S); Ischemia/Reperfusion group (I/R) with 30 minutes of renal ischemia; Remote ischemic perconditioning group (Per) with three cycles of 10 minutes of I/R performed during kidney ischemia; Tramadol group (T) treated with tramadol hydrochloride (40mg/kg); remote ischemic perconditioning + Tramadol group (Per+T) with both treatments. Oxidative stress was assessed after 24 hours of reperfusion. Results: Statistical differences were observed in MDA levels between I/R group with all groups (p<0.01), in addition there was difference between Tramadol with Sham, Per and Per+T groups (p<0.05), both in plasma and renal tissue. Conclusion: Remote ischemic perconditioning was more effective reducing renal ischemia-reperfusion injury than administration of tramadol or association of both treatments.